2018
DOI: 10.1111/ijsw.12323
|View full text |Cite
|
Sign up to set email alerts
|

Children placed in alternate care in Norway: A review of mental health needs and current official measures to meet them

Abstract: Children and youth placed in alternate care have often suffered detrimental care conditions before placement and the rupture of attachment bonds both before and during alternate care. In this article, we review the knowledge base on the prevalence of mental disorders, and access to mental health services, of children and youth in alternate care in Norway. Due to the increasing knowledge of this group's needs, official measures are now taken to improve service provision and cooperation between types and levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Previous studies from Norway have found that children and youth receiving IHS or who are placed outside their home display more mental health problems than peers from the general population (Havnen et al, 2009;Iversen et al, 2007). Studies have also documented a high prevalence of mental disorders among children and youth in FC, and it has been estimated that about 50% meet the criteria for one or more psychiatric disorders (Lehmann et al, 2013;Lehmann & Kayed, 2018). A study further found great variability in mental health adjustment over time among children and youth in FC (Havnen et al, 2014).…”
Section: The Norwegian Contextmentioning
confidence: 96%
“…Previous studies from Norway have found that children and youth receiving IHS or who are placed outside their home display more mental health problems than peers from the general population (Havnen et al, 2009;Iversen et al, 2007). Studies have also documented a high prevalence of mental disorders among children and youth in FC, and it has been estimated that about 50% meet the criteria for one or more psychiatric disorders (Lehmann et al, 2013;Lehmann & Kayed, 2018). A study further found great variability in mental health adjustment over time among children and youth in FC (Havnen et al, 2014).…”
Section: The Norwegian Contextmentioning
confidence: 96%
“…These teams should have a coordinating function between local authority levels of services and ambulatory teams in mental health services responsible for adolescents in institutional care. Furthermore, the report calls for commitment to cooperation agreements between CPS and mental health services (Directorate for health/BufDir, , 2017, but see Lehman & Kayed, 2018).…”
Section: Several Missing Links In the Cpsmentioning
confidence: 99%
“…There are indications that inter-agency collaboration between child welfare services (CWS) and child and adolescent mental health services improves early identification of mental health problems, as well as improved access to help (Bai, Wells, and Hillemeier 2009;Darlington and Feeney 2008;Timonen-Kallio 2019). Nevertheless, effective inter-agency collaboration has been reported to be difficult to achieve (Darlington and Feeney 2008;Stanley et al 2003), also in Norway (Lehmann and Kayed 2018;Jozefiak et al 2016;Pedersen 2019).…”
Section: Screening Of Mental Health Among Youth In Residential Care Imentioning
confidence: 99%